2012
DOI: 10.1007/s10142-012-0276-1
|View full text |Cite
|
Sign up to set email alerts
|

Genomic associations for drought tolerance on the short arm of wheat chromosome 4B

Abstract: Drought is a major constraint to maintaining yield stability of wheat in rain fed and limited irrigation agro-ecosystems. Genetic improvement for drought tolerance in wheat has been difficult due to quantitative nature of the trait involving multiple genes with variable effects and lack of effective selection strategies employing molecular markers. Here, a framework molecular linkage map was constructed using 173 DNA markers randomly distributed over the 21 wheat chromosomes. Grain yield and other drought-resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 85 publications
3
68
2
Order By: Relevance
“…However, MABC has only been rarely attempted for the improvement of drought tolerance in wheat on a large scale. For example, under the Generation Challenge Programme funded by CIMMYT, Mexico, and the National Initiative on Climate Resilient Agriculture Project supported by ICAR, India, efforts were made to introgress QTLs for several drought-related traits (canopy temperature, chlorophyll content, stay green habit, NDVI values, days to anthesis, grain yield, and its related traits) into two elite Indian wheat cultivars (HD2733 and GW322) through MABC [78] (for details of QTLs, see Kirigwi et al [46], Pinto et al [24], Kumar et al [53], and Kadam et al [69]). After foreground and background selection (90% recurrent parent), the BC 1 F 2 -and BC 2 F 2 -containing QTLs for drought-related traits and the 90% genome of the recurrent parent genotypes were advanced for seed multiplication.…”
Section: Marker-assisted Backcrossing (Mabc)mentioning
confidence: 99%
“…However, MABC has only been rarely attempted for the improvement of drought tolerance in wheat on a large scale. For example, under the Generation Challenge Programme funded by CIMMYT, Mexico, and the National Initiative on Climate Resilient Agriculture Project supported by ICAR, India, efforts were made to introgress QTLs for several drought-related traits (canopy temperature, chlorophyll content, stay green habit, NDVI values, days to anthesis, grain yield, and its related traits) into two elite Indian wheat cultivars (HD2733 and GW322) through MABC [78] (for details of QTLs, see Kirigwi et al [46], Pinto et al [24], Kumar et al [53], and Kadam et al [69]). After foreground and background selection (90% recurrent parent), the BC 1 F 2 -and BC 2 F 2 -containing QTLs for drought-related traits and the 90% genome of the recurrent parent genotypes were advanced for seed multiplication.…”
Section: Marker-assisted Backcrossing (Mabc)mentioning
confidence: 99%
“…QTLs for root traits have been reported on chromosomes 1B, 2A, 3B, 3D, 4A, 4B, 5D, 6A and 6B explaining up to 24.3 % of PV in wheat (Bai et al 2013;Liu et al 2013, Table 11.1). QTLs on 4BS explaining up to 14.5 % of PV have been identified in WL711/C306 RIL population for root traits and co-located with GY under drought stress during post-anthesis stage (Kadam et al 2012). Total of 9 QTLs for four root traits namely maximum root length, root biomass above 30 cm length, root biomass below 30 cm length and root: shoot ratio have been reported under irrigated and water stress condition.…”
Section: Root Traitsmentioning
confidence: 96%
“…The presence of strong GE interaction for these moisture stress adaptive traits signifies the importance of a separate breeding programme for drought tolerance. Recently, Kadam et al (2012) identified that drought-responsive shoot and root traits colocalize on same genomic regions. Chromosome 4B in wheat harbors QTLs for grain yield under drought, harvest index and root biomass, lateral root length, total root length and root tip number for seminal roots at seedling stage (Ren et al 2011;Kadam et al 2012).…”
Section: Pot Experimentsmentioning
confidence: 99%
“…Recently, Kadam et al (2012) identified that drought-responsive shoot and root traits colocalize on same genomic regions. Chromosome 4B in wheat harbors QTLs for grain yield under drought, harvest index and root biomass, lateral root length, total root length and root tip number for seminal roots at seedling stage (Ren et al 2011;Kadam et al 2012). Consistent genomic region associations for shoot and root traits for drought response will further improve the breeding efficiency.…”
Section: Pot Experimentsmentioning
confidence: 99%
See 1 more Smart Citation